(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The growth of society is analyzed by assessing the society’s established medical facilities; it is believed that a healthy society is the nation’s backbone. With technological breakthroughs, medical science is advancing, and numerous ailments are being recovered in less time. The study’s goal is to assess and highlight the many medical facilities and health care approaches that aid in the development of society. The study also aids in measuring the effectiveness of medical facilities supplied to patients to enhance their health. The usage of the Internet of Things (IoT) is rising day by day, assisting society in receiving medical assistance in an emergency and saving the lives of many people, as witnessed throughout the study. Different technologies are proving themselves in providing medical facilities from long distances which are observed in studies. Thus, it is said that the developing society has developed a healthcare system, which will be more developed with development in technology.